Análise da dinâmica costeira e vulnerabilidade do município de São Gonçalo do Amarante - Ce - Lopes, Debora Nogueira (2021)
The coastal zone corresponds to a common learned area converging in an occupation regime, at an increasingly accelerated pace, associated with development, industrialization, urbanization and tourist exploitation. Coastal morphological changes consist of a set of transformations triggered by natural and anthropic processes, which act at various temporal and spatial scales. It is in this environmental context that an area of study is inserted, in the municipality of São Gonçalo do Amarante, coast of the State of Ceará, in which integrated studies on the landscape took place, recognizing the structure, dynamics and its evolution, collaborating in the understanding of the relationship between man and the environment. Through the natural and environmental vulnerability of the municipality, through the integration of physical and anthropogenic characteristics, it was possible to determine that in the coastal portion of the municipality the predisposition of the environment to natural and anthropogenic factors and the susceptibility of the environment to anthropogenic pressures was very high. high. Subsequently, analysis of the behavior of the coastline in the last 36 years (1984-2020), through the analysis of multitemporal satellite images from the Landsat series with the aid of the DSAS extension of the ArcGis software using the linear regression rate method. In this analysis, it was possible to determine that the municipality of São Gonçalo do Amarante has undergone changes in local coastal dynamics and affected the natural capacity of systems to respond to extreme weather events, thus making these regions more vulnerable. Finally, based on the results obtained previously, the analysis of the Coastal Vulnerability Index (IVC) was defined, in order to assess the potential risk of natural events along the coast, and to identify and assess the elements and which factors increase or mitigate the effects of an extreme natural, technological or human event. Therefore, this thesis sought to analyze the environment in its broadest form, that is, to focus on analyzing natural and anthropogenic environmental components with a view to producing information and/or indicators that can help competent authorities and others to develop laws, plans, projects and programs that seek to improve the environmental quality of the location